Investigation And Evaluation of Various Parameters of the Anti-Asthmatic Pharmacological Activity of Araucaria Columnaris Leaf Extracts - Rawat, Devendra Kumar; Kumar Mohanty, Pradeep (Journal of Neonatal Surgery, 2025)
The study of botanical extracts to determine their antiasthmatic properties has gained attention in recent years. The current study used asthma models to examine the antiasthmatic properties of Araucaria columnaris leaf extract. The significance of A. columnaris Hook. for the treatment of asthma is unknown, despite the fact that it is notable for its profusion of bioactive chemicals that are derived from flavonoids, phenolics, terpenoids, steroids, and tannins. The effects of the leaf extract on milk-induced leukocytosis and catalepsy were the main subjects of the investigation. The ethanolic extract derived from the leaves of Araucaria columnaris (350mg/Kg) significantly mitigated catalepsy induced by clonidine and haloperidol in mice, indicating a possible antihistaminic effect. Furthermore, the ethanolic extract (350mg/Kg) has shown a statistically significant decrease in both total leukocyte and eosinophilia counts in a dose-dependent manner, suggesting its potential anti-allergic and anti-eosinophilic properties. This research adds to the investigation of natural treatments for asthma, highlighting the significance of A. columnaris as an antiasthmatic agent.